Hampered interest rate pass-through: A supply side story? - Lotta Heckmann; Julia Moertel (Deutsche Bundesbank, 2020)
This paper shows that the supply side of credit is a major factor for the phenomenonof hampered interest rate pass-through in monopolistic banking markets. Our data,covering all 1,555 small and medium sized banks in Germany, provides a clear wayto partial out demand shocks; we are thus able to show that while market-powerbanks charge higher loan rates, they spare their borrowers a part of exogenousupward shifts in the yield curve and furthermore withhold a substantial part ofrising market rates from their depositors. Because high market-power banks inour sample are relatively more profitable, they seem to be able to insure theirrelationship-customers against adverse shocks.
Keywords: E43; E51; E52; G21; 330; interest rate pass-through; bank competition; credit supply